2009
DOI: 10.1158/1541-7786.mcr-09-0187
|View full text |Cite
|
Sign up to set email alerts
|

UNC45A Confers Resistance to Histone Deacetylase Inhibitors and Retinoic Acid

Abstract: To identify potential biomarkers of therapy response, we have previously done a large-scale gain-of-function genetic screen to identify genes whose expression confers resistance to histone deacetylase inhibitors (HDACI). This genetic screen identified two genes with a role in retinoic acid signaling, suggesting that HDACIs target retinoic acid signaling as part of their anticancer effect. We study here a third gene identified in this genetic screen, UNC45A, and assess its role in retinoic acid signaling and re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
28
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 27 publications
5
28
0
Order By: Relevance
“…Our genetic results, which demonstrate the dual roles of UNC45b in affecting sarcomeric myosin and the GATA4 transcription factor during mouse cardiogenesis, are reminiscent of studies reporting the interactions of UNC-45A (A is for humans; a for other vertebrates) with the progesterone and glucocorticoid receptors (Chadli et al, 2006), and the retinoic acid receptor pathway (Epping et al, 2009). Both the hormone receptors and the retinoic acid receptor, like GATA4, perform significant roles in development and homeostasis.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Our genetic results, which demonstrate the dual roles of UNC45b in affecting sarcomeric myosin and the GATA4 transcription factor during mouse cardiogenesis, are reminiscent of studies reporting the interactions of UNC-45A (A is for humans; a for other vertebrates) with the progesterone and glucocorticoid receptors (Chadli et al, 2006), and the retinoic acid receptor pathway (Epping et al, 2009). Both the hormone receptors and the retinoic acid receptor, like GATA4, perform significant roles in development and homeostasis.…”
Section: Discussionsupporting
confidence: 65%
“…9A). As suggested by previous studies with the ubiquitously expressed homolog UNC-45A, its binding to the progesterone and glucocorticoid receptors (Chadli et al, 2006) and its effects on the retinoic acid receptor alpha isoform (Epping et al, 2009), we first demonstrated that UNC-45b participated in a complex with GATA4. Plasmids of UNC-45b-FLAG and GATA4-Myc were co-transfected into HeLa S3 cells.…”
Section: Interactions Between Unc-45b and Its Client Proteinssupporting
confidence: 51%
“…21 Additional putative targets for UNC-45A that may also be significant in breast and ovarian cancer progression are the progesterone and retinoic acid receptors. 39,42 UNC-45A proteins appear to be both regulated and putative regulatory molecules. Here, the UNC-45A 944-residue isoform is under an additional level of regulation, the presence of an additional proline-rich 15-amino-acid sequence, associated with its increased turnover through the ubiquitin-proteasome system.…”
Section: Discussionmentioning
confidence: 99%
“…The histone deacetylase inhibitor side-effect profile is low when compared with cytotoxic chemotherapy [20] . Moreover, two unbiased preclinical screens identified retinoid signal activation as the most effective method of augmenting the histone deacetylase inhibitor anti-cancer signal [21,22] . Retinoic acid receptor α (RARα), and, preferentially expressed antigen of melanoma, both repressor proteins for the retinoid signal, was shown to mediate resistance to histone deacetylase inhibitors [21] .…”
Section: Combination Therapy Improves the Anticancer Activity Of Histmentioning
confidence: 99%
“…Retinoic acid receptor α (RARα), and, preferentially expressed antigen of melanoma, both repressor proteins for the retinoid signal, was shown to mediate resistance to histone deacetylase inhibitors [21] . Furthermore, RARα-deficient cells showed enhanced sensitivity to histone deacetylase inhibitors in vitro and in vivo [22] . These studies suggest that retinoid signal activation is necessary for histone deacetylase inhibitor activity.…”
Section: Combination Therapy Improves the Anticancer Activity Of Histmentioning
confidence: 99%